Memristive devices based on graphene oxide. (April 2015) - Porro, Samuele; Accornero, Eugenio; Pirri, Candido Fabrizio; Ricciardi, Carlo
Abstract: Memristors are nanoscale devices able to generate intense fields by the application of relatively low voltages, which warrants peculiar properties such as fast, non-volatile and low-energy electrical switching, as well as the possibility of retaining their internal resistance state according to the history of applied voltage and current. Memristors are predicted to revolutionize the current approaches in computer electronics architecture with their application, for instance, as resistive random access memory. Moreover they are indicated as the first brick to create neuromorphic systems and artificial intelligence. The use of graphene oxide as active material for memristive switching systems offers an exciting alternative to other classes of materials, such as transition metal oxide and organic thin films. Graphene oxide is electrically insulating due to the presence of oxygen functionalities, with the advantage of being truly atomically-thin, which makes it the perfect candidate for the fabrication of memristive devices. Different mechanisms were recently proposed for graphene oxide memristive systems, but a definitive evidence in their support is still missing. This challenge has stimulated an extensive activity towards a robust and predictive understanding of the physical phenomena that lie behind this peculiar behavior. A comparative review of several graphene oxide memristive devices is here provided, with a distinction between two different mechanisms for resistance switching: oxygen ions drift and metal filament formation.